2020
DOI: 10.1002/ente.202000716
|View full text |Cite
|
Sign up to set email alerts
|

Sugars as Novel, Effective, and Renewable Hydrogen Sources in Dehydrogenation and Catalytic Transfer Hydrogenation Reactions

Abstract: The applications of sugars as inexpensive, renewable, and nontoxic sources of hydrogen gas are systematically demonstrated by means of dehydrogenation and catalytic transfer hydrogenation reactions. The chiral bifunctional Noyori‐type catalyst, Cp*Ir(TsDPEN), is found to effectively, regioselectively, and stereoselectively dehydrogenate various sugars possessing different steric hindrance and stereochemistry. Furthermore, kinetics experiments for these dehydrogenation reactions reveal that many sugars are supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Thananatthanachon and co‐workers systematically demonstrated the potential applications of sugars as inexpensive and non‐hazardous sources of hydrogen for catalytic transfer hydrogenation and dehydrogenation reactions [99] . A series of ruthenium and iridium bifunctional Noyori‐type complexes, containing diamido ligands, were evaluated for their efficacy in the dehydrogenation of various sugars and the reduction of various aldehydes and ketones via the TH strategy.…”
Section: Transfer Hydrogenation Using Carbohydrates As Hydrogen Donormentioning
confidence: 99%
See 1 more Smart Citation
“…Thananatthanachon and co‐workers systematically demonstrated the potential applications of sugars as inexpensive and non‐hazardous sources of hydrogen for catalytic transfer hydrogenation and dehydrogenation reactions [99] . A series of ruthenium and iridium bifunctional Noyori‐type complexes, containing diamido ligands, were evaluated for their efficacy in the dehydrogenation of various sugars and the reduction of various aldehydes and ketones via the TH strategy.…”
Section: Transfer Hydrogenation Using Carbohydrates As Hydrogen Donormentioning
confidence: 99%
“…Thananatthanachon and co-workers systematically demonstrated the potential applications of sugars as inexpensive and non-hazardous sources of hydrogen for catalytic transfer hydrogenation and dehydrogenation reactions. [99] A series of ruthenium and iridium bifunctional Noyori-type complexes, containing diamido ligands, were evaluated for their efficacy in the dehydrogenation of various sugars and the reduction of various aldehydes and ketones via the TH strategy. Among the complexes considered, Ir17, namely [Cp*Ir(TsDPEN)], exhibited the highest efficiency for the dehydrogenation processes, achieving complete conversion of D-glucose to D-gluconopyranolactone in DMSO as solvent (Scheme 45).…”
Section: Transfer Hydrogenation Using Carbohydrates As Hydrogen Donormentioning
confidence: 99%
“…[13,14] Hence, sugars can logically be able to function as efficient hydrogen donors. [15] It was reported by Fujita and his co-workers that the reaction of Dglucose in water under reflux for 20 h in the presence of [Cp*Ir(6,6'-dihydroxy-2,2'-bipyridine)(H 2 O)][OTf] 2 could result in the production of hydrogen gas in 95 % yield. [16] Yoshida et al utilized two equivalents of glucose as the hydrogen donor to convert various ketones and aldehydes to corresponding alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, sugars usually exist in the solution in cyclic form (pyran or furan ring), and the H connected to the hemiacetal carbon (α‐H of the terminal carbon) is very active, thus can be easily removed to obtain lactones and hydrogen [13,14] . Hence, sugars can logically be able to function as efficient hydrogen donors [15] . It was reported by Fujita and his co‐workers that the reaction of D‐glucose in water under reflux for 20 h in the presence of [Cp * Ir(6,6′‐dihydroxy‐2,2′‐bipyridine)(H 2 O)][OTf] 2 could result in the production of hydrogen gas in 95 % yield [16] .…”
Section: Introductionmentioning
confidence: 99%
“…9 Yoshida et al developed Ircatalyzed transfer hydrogenation using glucose as the hydrogen donor for carbonyl group reduction. 10 Furthermore, Lamberson et al reported catalytic transfer hydrogenation using glucose as the hydrogen source 11 Although a few direct hydrogenation reactions using biomass have been accomplished over complex noble-metal catalysts, [9][10][11] these methods mostly rely on homogenous catalysis, which lead to issues such as catalyst handling and recycling.…”
mentioning
confidence: 99%